1986
DOI: 10.1094/pd-70-106
|View full text |Cite
|
Sign up to set email alerts
|

Populations, Pathogenicity, and Benomyl Resistance ofBotrytisspp.,Penicilliumspp., andMucor piriformisin Packinghouses

Abstract: house were selected on each sampling Spotts, R. A, and Cervantes, L. A. 1986. Populations, pathogenicity, and benomyl resistance of date for pathogenicity tests. To determine Botrytis spp., Penicillium spp., and Mucorpiriformis in packinghouses. Plant Disease 70:106-108. pathogenicity, Anjou pear fruits were disinfested with 95% ethanol and Populations of Botrytis spp., Penicillium spp., and Mucorpiriformis were determined during two inoculated with each isolate by placing seasons in air and dump-tank water of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(78 citation statements)
references
References 0 publications
2
71
0
5
Order By: Relevance
“…Postharvest application of fungicides can minimize the incidence of decay, but frequent use may result in fungicide resistance. For example, Botrytis developed resistance to benomyl (Rosenberger and Meyer 1979;Spotts and Cervantes 1986).…”
Section: Mots Clésmentioning
confidence: 99%
See 1 more Smart Citation
“…Postharvest application of fungicides can minimize the incidence of decay, but frequent use may result in fungicide resistance. For example, Botrytis developed resistance to benomyl (Rosenberger and Meyer 1979;Spotts and Cervantes 1986).…”
Section: Mots Clésmentioning
confidence: 99%
“…Postharvest application of fungicides can minimize the incidence of decay, but frequent use may result in fungicide resistance. For example, Botrytis developed resistance to benomyl (Rosenberger and Meyer 1979;Spotts and Cervantes 1986).Acetic acid and ethanol are universal metabolic intermediates and occur naturally in many fruits (Nursten 1970). Sholberg and Gaunce (1995) found that low concentrations of acetic acid in air were extremely effective for controlling B. cinerea conidia on apple fruit, and did not have phytotoxic effect.…”
mentioning
confidence: 99%
“…However, their use can be both non-economical, when the cost of treatment exceeds the loss from rot, and dangerous, because of the risk to select resistant strains by reiterated applications [4]. Moreover, Chitosan hydrochloride solution (1 g/L) was prepared by dissolving the polymer in deionized water under magnetic stirring for 2 h at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Fungicide treatment is the most common strategy used to control this pathogen, but the intensive use of fungicides such as thiabendazole (TBZ) and imazalil (IMZ) has led to the emergence of resistant strains of P. expansum (Spotts and Cervantes 1986;Vinãs et al 1993;Guetsky et al 2001). This fact, associated with growing public concern for human health and environmental hazards, highlights the need to develop alternative methods for controlling post-harvest diseases of apples (Wisniewski and Wilson 1992;Smilanick 1994).…”
mentioning
confidence: 99%